HALL CONDUCTIVITY ESTIMATES FROM MAGNETOTELLURIC SOUNDING DATA - V. Plotkin; V. V. Potapov (Геодинамика и тектонофизика)
Many minerals have semiconductor properties. It is known that petroleum reservoir rocks permeated with hydrocarbon fluids can sometimes behave as semiconductors. In the Earth’s magnetic field, the electrical conductivity of such materials becomes anisotropic, and the Hall effect is quite possible in rocks in natural conditions and detectable by magnetotelluric sounding. In the anisotropic medium, the field is subject to normal mode splitting, and its components show different attenuation coefficients and phase velocities. The modes differ due to polarization and rotation of the field vectors (clockwise in one mode, and counterclockwise in another). With account of the Hall effect, responses of the medium can be different when the medium is excited by a single normal wave. To detect the Hall effect in MTS surveys, we use the polarization analysis method and select the spectra of modes with right and left circular polarization. Special experiments were carried out to detect the contribution of the Hall effect during the MTS surveys. This article presents the first estimates of the Hall conductivity for the studied rocks.